Allergic rhinitis: diagnosis and management. (2nd February 2022) - Siddiqui, ZA; Walker, A; Pirwani, MM; Tahiri, M; Syed, I
Abstract : Allergic rhinitis affects 20% of the population of the UK. It confers a significant health burden upon the individual as it affects the patient's quality of life and is associated with serious comorbidities including asthma, sinusitis and conjunctivitis. Owing to its prevalence, it has a significant economic impact through its effects on education, productivity and use of healthcare resources. This review focuses on the management of allergic rhinitis and potential future treatments, because of the lack of clear national guidelines and because this illness is often misdiagnosed and mismanaged. The article provides a comprehensive overview of allergic rhinitis and illustrates the assessment criteria for various subcategories.